Comparison of a Novel Multiple Marker Assay Versus the Risk of Malignancy Index for the Prediction of Epithelial Ovarian Cancer in Patients with a Pelvic Mass - MOORE, Richard G. (2010)
OBJECTIVES: To compare the Risk of Malignancy Index (RMI) to the Risk of Ovarian Malignancy Algorithm (ROMA) to predict EOC in women with a pelvic mass. STUDY DESIGN: 457 women with imaging results from ultrasound, CT and MRI, and serum HE4 and CA 125 determined prior to surgery for pelvic mass were evaluable. RMI values were determined using CA 125, imaging score and menopausal status. ROMA values were determined using HE4, CA 125, and menopausal status. RESULTS: At a set specificity of 75%, ROMA had a sensitivity of 94.3% and RMI had a sensitivity of 84.6% for distinguishing benign from EOC (p=0.0029). In patients with stage I and II disease, ROMA achieved a sensitivity of 85.3% compared with 64.7% for RMI (p<0.0001). CONCLUSIONS: The dual marker algorithm utilizing HE4 and CA125 to calculate a ROMA value achieves a significantly higher sensitivity for identifying women with EOC than does RMI.